E-LEARNING STRATEGY AT TECHNICAL UNIVERSITY - Michail A. Solov’Yov; Sergey I. Kachin; Svetlana B. Veledinskaya; Margarita Yu. Dorofeeva (Высшее образование в России, 2016)
The paper explores emerging trends of modern society that have created tremendous impacts on higher education, both in worldwide and national scales. Implementing e-learning initiatives as the response of higher education institutions to major challenges isdiscussed. Educational process reforming through the use and development of e-learning technologies at the National Research Tomsk Polytechnic University is shown.